Current Practices in Pharmacology Education Across Doctor of Audiology Programs. - Le Prell, Colleen G.; McKenna, Nancy; DiSogra, Robert M.; Libman, Dana; Atcherson, Samuel R. (American Journal of Audiology, 2026)
Purpose: Accrediting bodies for Doctor of Audiology (AuD) programs require students to develop competencies related to pharmacological agents and their effects on hearing and balance. This study was designed to assess education on pharmacology in AuD programs. Method: The scope of pharmacology education within AuD curricula was surveyed in 2021-2022 using a survey distributed online to program directors across the United States. Results: About one third of the AuD programs in the United States and Puerto Rico offered a dedicated pharmacology course. Other AuD programs reported that they embedded pharmacology education within the rest of the curriculum. Among colleges/universities offering a pharmacology course, the content included was variable. Review of the content in pharmacology showed little consistency in how pharmacological topics are addressed across programs. Conclusions: The current accreditation standards for AuD programs require knowledge of the effects of pharmaceutical compounds on hearing and balance but provide little specific guidance. More consistency in the education of future audiologists with respect to pharmacological foundations has the potential to benefit patients.